Small-Area Analysis of Incidence and Localisation of Vulvar Cancer. (22nd June 2010) - Baumann, Klaus H.; Müller, Olga; Naujok, Helke B.; Mann, Ellen; Barth, Peter; Wagner, Uwe
Abstract : Objective . Vulvar cancer is a rare disease mainly in older women. HPV and non-HPV induced vulvar cancer reflect two types of oncogenesis. Controversies exist on most recent developments in vulvar cancer incidence, patients, and disease characteristics. Changes in incidence, age of disease onset, and tumor site in women treated for primary vulvar cancer in a single German university hospital unit will be described. Methods . A retrospective analysis of patient records of women treated between 1994 and 2008 was performed. The fifteen-year-spanning period was divided into three five year-spanning cohorts. Descriptive and statistical analyses were performed. Results . 104 patients were identified: cohort-1 from 1994 to 1998 (11 patients); cohort-2 from 1999 to 2003 (21 patients); cohort-3 from 2004 to 2008 (72 patients). Mean age (years) was 73.18 (confidence interval (CI): 64.04; 82.33), 58.9 (CI: 52.24; 65.57), and 61.19 (CI: 57.27; 65.12), respectively. Vulvar cancer confined to the region between clitoris and urethra was seen more often in cohort-3 (n = 20 ) compared to cohort-1 (n = 0 ) or cohort-2 (n = 1 ). Conclusion . This analysis supports the notion of rising incidence of vulvar cancer and a changing pattern of anatomical local extension. Disease onset is not restricted to older women.